Egg-laying Behavior and Nest Physical Characteristics of Maleo Bird (Marcocephalon maleo) in Panua Nature Preserve, Maleo Village, Paguat District - Muhi, Febrianti; Baderan, Dewi Wahyuni K. Baderan; Ibrahim, Mustamin (Metamorfosa: Journal of Biological Sciences, 2021)
The study aimed to identify the egg-laying behavior and characteristic of the nest of Maleo birds. The survey study conducted first-hand direct observation based on the facts at the site. An explorative method was employed to acquire the data of nest characteristics. The method refers to the exploration of the laying nest and measurement of physical characteristics of the nest that contains the egg. The results revealed that the Maleo bird’s egg-laying behavior comprised: digging hole, tracing for any potential dangers, caching, looking for good, perching, finding a good location, roosting, playing, and dancing. The characteristics of laying nest of Maleo bird in the research site were as follows: 1) the average nest depth and width was 65 cm and 62 cm respectively; 2) the average temperature of laying nest hole from morning until afternoon was at 31.75-33.6 º C, while the average temperature of the nest surface was at 27.5-50.5 º C. Other environmental factors comprised: 20-35% humidity rate, acidity (pH) of seven, while the main constituents of nest were 98-100% sand, 0-2% dusts, and 0% clay. The bird’s dominant egg-laying behavior was digging hole.   Keyword : characteristics, Marcocephalon maleo, behavior, nest